Improving Discipline and Responsibility of Student Learning Through Project Assessment - Mania, Sitti (Al-Ulum, 2015)
This âclassroom action researchâ aims to determine the effectiveness of the project assessment at Islamic Junior School (Madrasah Tsanawiyah) Model Makassar in the VIII/a class as subject research. The study carried out in two cycles, data collection was done by employing three ways: questionnaires, observation and test administration. The result showed that the project assessment was able to improve: 1) student discipline, shown on average 73,78% of the first cycle and the second cycle was 91,72%. 2) Responsibility for student learning, the average seen in the first cycle of 66,37% and 85,77% for the second cycle. 3) Student learning outcomes, the first cycle were 51,72% while in the second cycle there was 17,24% score below the minimum completeness criteria. On the individual test conducted at the end of the second cycle showed that there are only 4 students (13,79%) who had not reached the minimum completeness criteria.-----Penelitian tindakan kelas ini bertujuan untuk mengetahui keefektifan penilaian proyek dalam meningkatkan disiplin dan tanggung jawab belajar siswa. Penelitian dilakukan pada Madrasah Tsanawiyah Model Makassar dengan subyek penelitian siswa kelas VIII/a. Tindakan dilakukan dalam dua siklus, pengumpulan data dilakukan dengan menggunakan tiga cara yaitu angket, observasi dan pemberian tes. Hasil penelitian menunjukkan bahwa teknik penilaian proyek mampu meningkatkan: 1) disiplin siswa, terlihat pada rata-rata siklus pertama sebesar 73,78% dan pada siklus kedua sebesar 91,72%. 2) tanggung jawab belajar siswa, terlihat pada rata-rata siklus pertama sebesar 66,37 dan pada siklus kedua sebesar 85,77. 3) hasil belajar siswa, siklus pertama terdapat 51,72% sedangkan pada siklus kedua terdapat 17,24% skor di bawah kriteria ketuntasan minimal. Pada tes individu yang dilakukan pada akhir siklus II hanya terdapat 4 siswa (13,79%) yang belum mencapai kriteria ketuntasan minimal.Â